Translation as a Paradigmatic Universal, Post-Industrial, Knowledge-Based and Innovative Service - Kuźnik, Anna (2014)
In this paper I argue that translation activity, in all its oral and written forms, is a paradigmatic universal, post-industrial, knowledge-based and innovative service in very advanced societies and economies. I base this argument on general social and economic concepts that are little known in the field of T ranslation Studies, and which revolve around the following topics: (1) definition, characteristics and type of services sector; (2) global tendencies related to the services sector; and (3) innovation in the services sector. The fact that translation services are contemporary services par excellence leads to certain problems for measuring them. In conclusion, I mention three principal consequences of such a fact for research in other disciplines, for research in Translation Studies and for the training of translators. This paper can be considered as a basis for future research that could focus more on the present and future of translation services.
Keywords: innovation; knowledge-based services; translation services; services sector